Three new genera and three new species of Lasiopteridi (Diptera: Cecidomyiidae) on Rubiaceae from Guadeloupe, French West Indies, and a key to genera of Neotropical Lasiopteridi unplaced to tribe - Gagné, Raymond J.; Etienne, Jean (Zootaxa, 2015)
Three new genera of Lasiopteridi (Diptera: Cecidomyiidae), Faramitella Gagné, new genus, Anapeza Gagné, new genus, and Pellacara Gagné, new genus, each with one new species, are described. The new species are from leaf galls on Rubiaceae collected in Guadeloupe, F.W.I.: Faramitella planicauda Gagné, new species, was reared from Faramea occidentalis (L.) A. Rich.; Anapeza tumida Gagné, new species, and Pellacara postica, new species, were both reared from Psychotria mapourioides DC. The three new genera belong to Lasiopteridi but are unassigned to tribe. A key to the adult stage of these and 23 other Neotropical genera of unplaced Lasiopteridi whose adults are known is provided.